Customer-Based Market Positions of Domestic Airlines in Turkey - Meltem Caber (Journal of Tourismology)
Increasing competition between legacy and low-cost domestic airlines in many countries has made it more important to understand traveler choices, perceptions, preferences, and behavioral intentions. This study aims to assess customerbased market positions of domestic airlines in Turkey. Data obtained from 202 university students were used to generate comparative market positioning maps in order to explore the position of each airline company. The results show that Turkish Airlines had better positions than other airlines in regard to several competitiveness indicators (e.g. quality, price, and favorite travel choice). This finding emphasizes the competitive advantage of legacy domestic airlines as against that of low-cost airlines.